Life Cycle Assessment to Compare the Environmental of Food Waste Management System in Semarang City - Syahrul Al Qadar; Mochamad Arief Budihardjo; Ika Bagus Priyambada (Universitas Diponegoro, 2024)
1.3 billion tons of the food produced for human consumption is wasted in the food supply chain as a result of a number of issues. A high proportion of food waste occurs during consumption, primarily influenced by consumer behavior. In Semarang City, Black Soldier Fly, incineration, and composting are alternatives to food waste management. This research aims to analyze alternative food waste management methods that yield reusable resources and materials because currently unknown which method has the smallest environmental impact. Life Cycle Assessment method can be used to examine the environmental impact of the food waste management system from every phase 1 ton food waste analyze. BSF has proven superior to composting, incineration and landfilling methods in analyzes of potential environmental impacts that reduce 90% environmental impact. Landfills cover a large area and the effect of global warming is significant until of 1.704E+03 CO2-eq, this issue needs more attention in the management of the generated CH4. Incineration needs to make advances in the method such as producing new resources and emissions so that can be reused because incineration impact eutrophication potential until 2.438E+00 . For reasons environmental concerns, efficient food waste management is crucial to realizing the Sustainable Development Goals.